Dampak Atraksi dan Aksesibilitas terhadap Minat Kunjungan Wisatawan di Desa Wisata Sembungan Kabupaten Wonosobo - Ernes Septina Azizi; Anggi Fitria Cahyaningsih; Gigieh Henggar Jaya; Faishal Permana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the impact of attractions and accessibility on tourist visitation interest in Sembungan Tourism Village, Wonosobo Regency. Sembungan Tourism Village is the highest village in Java Island with an altitude of 2,300 meters above sea level, featuring tourist attractions such as Sikunir Hill, Cebong Lake, Sikarim Waterfall, and the traditional Gimbal Hair Cutting ceremony. The research employed a quantitative approach with accidental sampling technique involving 100 respondents. Data analysis used multiple linear regression. The results show that attractions positively and significantly influence visitation interest with t-value 3.613 > t-table 1.985 (significance 0.000). Accessibility also has a positive and significant influence with t-value 2.760 > t-table 1.985 (significance 0.007). Simultaneously, attractions and accessibility significantly influence visitation interest with F-value 18.886 > F-table 3.09 (significance 0.000) and a determination coefficient of 0.280. The management of Sembungan Tourism Village needs to improve the quality of attractions and accessibility to increase tourist visitation interest through diversification of attractions and improvement of transportation infrastructure.